Spoken Corrective Feedback in Offline Speaking Lessons at MNC University - aiddin, Malevna baha; Arianti, Theresia (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2024)
This study needs to be conducted because the teacher as a facilitator plays an important role in providing feedback and giving additional information in the form of an explanation regarding errors in giving verbal motivation. This research aims to fulfill some objectives: 1) To investigate the kinds of corrective feedback that are most frequently utilized by the lecturer at MNC University 2) To analyze the reasons why the lecturer used this type of spoken corrective feedback in speaking classes at MNC University. This research used descriptive qualitative research approach. This study reveals that explicit with metalinguistic feedback was the most used type of feedback found; linearity between the feedback and students’ needs and objectives is the main reason why the lecturer prefers this type of feedback.